Philosophy and the ecological problems of civilisation - Ursul, A.D (ed.); Creighton, H. Campbell (tr.) (Moscow, 1983)
This book is the fruit of the reflections of a group of soviet philosophers and specialists in ecological problems, and was prepared for the 17th World Congress of Philosophy , whose main them is Philosophy and Culture. It can perhaps be considered a concentrated expression of the whole aggregate of the global problems of the present socio-physical cycle. It is devoted to a theme that can be termed philosophical comprehension of the culture of the interaction of civilization and nature.
Keywords: "Institute of Philosophy, IJSSR Academy of Scinces"